2023
DOI: 10.22331/q-2023-02-16-922
|View full text |Cite
|
Sign up to set email alerts
|

Graph-theoretic approach to Bell experiments with low detection efficiency

Abstract: Bell inequality tests where the detection efficiency is below a certain threshold ηcrit can be simulated with local hidden-variable models. Here, we introduce a method to identify Bell tests requiring low ηcrit and relatively low dimension d of the local quantum systems. The method has two steps. First, we show a family of bipartite Bell inequalities for which, for correlations produced by maximally entangled states, ηcrit can be upper bounded by a function of some invariants o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…On the theory side, the analysis of the studied schemes is tight when considering CHSH-based protocols. To improve the performance, more sophisticated protocols including e.g., twoway classical communication in the post-processing stage 146 or exploiting higher-dimensional Bell inequalities 90,91 might be an option, though they seem to be challenging at the moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the theory side, the analysis of the studied schemes is tight when considering CHSH-based protocols. To improve the performance, more sophisticated protocols including e.g., twoway classical communication in the post-processing stage 146 or exploiting higher-dimensional Bell inequalities 90,91 might be an option, though they seem to be challenging at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…81 ). In this respect, it has been shown that higher-dimensional Bell inequalities offer lower minimum efficiencies and better robustness to noise than the CHSH inequality (see for instance 85,90,91 ). Note, however, that solutions like these rely on the possibility of entangling two particles in higher-dimensional degrees of freedom, which is a more complex task from an experimental point of view.…”
Section: Protocol Improvements and Variantsmentioning
confidence: 99%
“…This demands a detection efficiency above a certain threshold η crit [14] that depends on the nonlocal correlations. Recently [15,16], several bipartite quantum correlations between highdimensional quantum systems have been identified requiring η crit smaller than those needed for qubits [17,18] and ququarts [19], which are the systems used in the detection-loopholefree Bell tests performed so far [20][21][22][23][24][25][26][27]. However, for all these cases, achieving a small detection efficiency requires a large number of settings.…”
Section: A Motivationmentioning
confidence: 99%
“…[15], each party has to measure 2 8 settings; to achieve η crit = 0.324 in Ref. [16], each party has to measure 2 30 settings. These correlations need too many settings to be useful for actual experiments.…”
Section: A Motivationmentioning
confidence: 99%
See 1 more Smart Citation